Method of Mathematical Modeling in the Study of Differential Equations Based on Professional Orientation - Khursanalievich, Khonkulov Ulugbek; kizi, Rasulova Farida Farhodjon (Research Parks Publishers, 2023)
the article reveals the importance of the method of mathematical modeling in the study of differential equations based on their profession. In the process of studying differential equations of certain processes occurring in the fields of chemistry, mathematical models are given as an example.